Elaborar un plan de contingencia para evitar el Síndrome de Burnout en los médicos legistas de la fiscalía general del estado basado en el estudio de la incidencia de los factores psicosociales de riesgo. - Alomoto Salazar, Alejandro Adolfo (2018)
or the systematization of the intervention work we will review the phase of the project that was carried out through the activities aligned to the fulfillment of the proposed objectives. The application of the evaluation of psychosocial risk factors to the Legislative Physicians included in the list of beneficiaries of this project was carried out as an initial activity. The test applied to the evaluation is the psychosocial factor test F-PSICO, which will help to give a quantitative diagnosis about the psychosocial risk factors present in the position of Legista Medical, which gives us a clearer and more complete picture about the conditions in which the professionals of that position develop. With the results obtained from the application of the F-PSICO test, the test was scored, from which the psychosocial risk factors present were obtained, from which the factors that were found with "very high" risk scores were selected. the highest scale of the qualification levels of the test to later relate them to the presence of the Burnout syndrome in the professionals who perform the position of Legislative Physicians. It was concluded with the elaboration of the action plan based on the results obtained from the analysis of the risk factors.